Предмет:
МатематикаАвтор:
анонимРешим уравнения:
1) √(2 * х - 1) = х - 2;
Возведем уравнение в квадрат и тогда получим:
√(2 * x - 1)^2 = (x - 2)^2;
2 * x - 1 = (x - 2)^2;
2 * x - 1 = x^2 - 2 * x * 2 + 2^2;
2 * x - 1 = x^2 - 4 * x + 4;
x^2 - 4 * x + 4 - 2 * x + 1 = 0;
x^2 - 6 * x + 5 = 0;
D = b^2 - 4 * a * c = (-6)^2 - 4 * 1 * 5 = 36 - 20 = 16;
x1 = (6 - √16)/(2 * 1) = (6 - 4)/2 = 2/2 = 1;
x2 = (6 + √16)/(2 * 1) = (6 + 4)/2 = 10/2 = 5;
Ответ: х = 1 и х = 5.
2) √(х^2 + 3 * х – 4) = √(2 * х + 2);
x^2 + 3 * x - 4 = 2 * x + 2;
x^2 + 3 * x - 4 - 2 * x - 2 = 0;
x^2 + x - 6 = 0;
D = 1 - 4 * 1 * (-6) = 25;
x1 = (-1 + 5)/2 = 4/2 = 2;
x2 = (-1 - 5)/2 = -6/2 = -3;
Ответ: х = 2 и х =-3.
Автор:
houston9hksДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть